Chemical composition and biological activities of the essential oils from different parts of Ferulago trifida Boiss. Issue 5 (3rd September 2017) - Tavakoli, S.; Yassa, N.; Delnavazi, M. R.; Akhbari, M.; Hadjiakhoondi, A.; Hajimehdipoor, H.; Khalighi-Sigaroodi, F.; Hajiaghaee, R.
Abstract: As a result of GC and GC-MS analysis of the essential oils from different parts of Ferulago trifida Boiss., a total of thirty-three compounds were identified in the flowers (Fl), stems (S), leaves (L) and fruits (Fr) essential oils, of which (E)-β-ocimene (Fl: 37.3, S: 20.7, L: 25.7, Fr: 30.5%), α-pinene (Fl: 16.3, S: 22.6, L: 19.6, Fr: 18.0%) and bornyl acetate (Fl: 9.4, S: 8.5, L: 16.7, Fr: 11.0%) were main compounds. Among the thrity-eight compounds identified in the roots essential oil, suberosin (20.7%), β-barbatene (6.6%) and cuparene (6.1%) were main compounds. All essential oils exhibited weak DPPH free radical scavenging activity (IC50 : 95–120 µg ml −1 ). Among the tested samples flowers, fruits and roots essential oils by 72.1, 78.7 and 74.3% inhibition of Ach Enzyme, respectively, exhibited considerable AChE inhibitory effects in Elman method. They had moderate cytotoxic activity (IC50 : 15–55 µg ml −1 ) on cancerous cell lines (MCF-7, A-549 and HT-29) in MTT assay.